2007
DOI: 10.1007/s11605-006-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-Like Molecule Alpha Reduces Gallbladder Optimal Tension

Abstract: These data suggest that in nondiabetic lean mice: 1) resistin does not alter insulin resistance or gallbladder optimal tension, but 2) RELM-alpha increases insulin resistance and reduces gallbladder optimal tension. Therefore, we concluded that RELM-alpha may play a role in insulin-resistance mediated gallbladder dysmotility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…In addition, recent reports that overweight Crohn's disease patients (body mass index >24) develop more severe disease (as indicated by more frequent anoperineal complications, a marked year-by-year disease activity and require earlier surgical intervention), compared with lean patients (35, 36). In agreement with our data, a recent study by Al-Azzawi et al demonstrated that prolonged administration of intraperitoneal Relm-α (but not resistin), significantly increased insulin resistance that is associated with decreased gallbladder tension (37). Thus, while Relm-α and resistin share similar structure and expression pattern, they may have distinct roles under different settings.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, recent reports that overweight Crohn's disease patients (body mass index >24) develop more severe disease (as indicated by more frequent anoperineal complications, a marked year-by-year disease activity and require earlier surgical intervention), compared with lean patients (35, 36). In agreement with our data, a recent study by Al-Azzawi et al demonstrated that prolonged administration of intraperitoneal Relm-α (but not resistin), significantly increased insulin resistance that is associated with decreased gallbladder tension (37). Thus, while Relm-α and resistin share similar structure and expression pattern, they may have distinct roles under different settings.…”
Section: Discussionsupporting
confidence: 93%
“…[28][29][30][31] These inflammatory changes predispose to GD by impairing the muscle cell function of the gallbladder wall resulting from increased insulin resistance, and by impairing absorptive and secretive functions of the gallbladder. [32][33][34] Our results support this theory as FGV was found to be increased in patients with NAFLD, possibly due to the decreased absorptive function of gallbladder. A recent study by Pellegrinelli et al 33 has indeed shown that inflammation caused by human adipocytes causes decreased expression of contractile proteins in myotubes.…”
supporting
confidence: 81%
“…Furthermore, hepatic insulin resistance in a mouse model has been identified as the molecular link between MS and risk of cholesterol gallstones, by way of its ability to increase biliary cholesterol secretion [28]. Increased hepatic cholesterol secretion, supersaturation of bile and gallbladder dysmotility are all exacerbated with conditions of the MS, providing the ideal setting for the development of gallstones [73]. Interestingly, an alarmingly high prevalence of the MS is observed in societies where ‘westernized’ nutrition prevails and its dietary constituents, e.g.…”
Section: Lifestyle Factorsmentioning
confidence: 99%